Mental health problems raise the odds of cognitive impairment in COVID-19 survivors - Chakrabarty, Madhushree; Chatterjee, Piali; Mukherjee, Adreesh; Das, Gautam; Mollah, Rafikul Islam; Mondal, Banshidhar; Sardar, Swarup; Basu, Ayanendranath; Ghosh, Mrinalkanti; Sengupta, Amitabha; Pal, Sankar K.; Biswas, Atanu (Frontiers in Psychiatry, 2024)
Background COVID-19 survivors around the globe are suffering from mental health issues. While mental health problems can be an early warning sign of dementia, they may also increase the chances of developing the disease. In this study, we examined the mental health of COVID-19 survivors and mapped its associations with cognitive and demographic variables. Method COVID-19 survivors listed in the databases of three tertiary care hospitals in Kolkata were contacted sequentially. 376 willing patients were interviewed over the telephone. 99 COVID-19 patients and 31 matched controls participated in the in-person interviews that were arranged for a more detailed investigation. The participants were administered standardized tests that are widely used for the assessment of cognitive functioning and mental health status. Result 64.89% of COVID-19 survivors reported a deterioration in physical functioning. 44.95% reported a decline in mental health, whereas 41.49% reported a drop in cognitive performance. Detailed investigations revealed that they had an increased risk of having depression, anxiety, and poor sleep quality by 91%, 68%, and 140%, respectively. 6.1% of the patients had mild cognitive impairment, and 4% had dementia. COVID-19 patients who had depression and anxiety were 8.6 and 19.4 times more likely to have cognitive decline, respectively. Compared to the matched controls, COVID-19 patients had greater depression (p<.001), anxiety (p<.001), stress (p =.003), and insomnia (p <.001). They also scored significantly lower on Addenbrooke’s Cognitive Examination-III (p =.009) and Picture Naming Test (p =.005) and took significantly longer to complete Trail Making Test-A (p =.002). Conclusion COVID-19 survivors in this study had major mental health issues even one year after contracting the virus. They had significant cognitive deficits that might progress into dementia. Strict monitoring and systematic treatment plans should be implemented as soon as possible.